Shock wave interaction with porous compressible foams - Atkins, Mark D (My University, 2016)
Two foams, a polyether (density 32.5 kg/m3) and a polyester (density 38 kg/m3) foam were tested in a shock tube to analyze the interaction of a normal shock wave and a compressible porous material. The foam specimens were placed in the shock tube test section! the foam being bounded by two steel walis, two glass windows and a solid back plate. The compression chamber of the shock tube was pressurized and the diaphragm separating the compression chamber and the expansion chamber was ruptured, thus producing a normal shock wave which travels down the shock tube and strikes the foam. Piezoelectric pressure transducers 'vvera used to record the pressure before, alongside and behind the foam. A complete set of schlieren photographs, recording the interaction of the incident shock wave and the porous material were taken for each foam. A method ,tortracking the path of particles of foam (path photographs) was developed. Combining the information obtained from the pressure records, schlieren photographs and path photographs a complete picture of the shock wave foam interaction was developed. All the gas waves were identified and analyzed, A foam wave (velocity 90 m/s) travelling through the skeleton of the material was discovered. A physical model was developed to explain the high pressure recorded behind the foam. This model is based upon the foam being compressed and forming an almost solid piston, thus forcing the trapped gas into a diminishing volume and creating a high pressure behind the foam. The theoretical analyses of Monti (30), Gel'fand (20) and IBvozdeva (22) were analyz.ed and compared. The general finding was that for the range of incident mach numbers 1.~i1 to 1.46 Monti's analysis under predicts the reflected Mach number by 3 % and Gel'fand's analysis over predicts the reflected Mach number by 6 %. The coefficient of pressure increase (the ratio of the maximum pressure recorded behind the foam to the equivalent pressure recorded during ~he reflection of a shock wave from a solid wall) as predicted iJy Gvoz.deva's ane.lysisfor the polyether foam lies wjthin the scatter of the experimental results. However for the polyester foam Gvozdeva's analysis under predicts the coefficient of pressure increase by 15%.
Keywords: Shock waves; Foamed materials; Compressibility; Explosions; Porous materials